Laparoskopska kolorektalna kirurgija v Splošni bolnišnici Brežice - Zanchi, Pero (Endoskopska revija, 2011)
Laparoscopic management of colorectal diseases has been gaining popularity because of its wellknown advantages, including less invasiveness, less pain, shorter hospital stay, faster recovery, and smaller operative wound. Studies have shown that hospital size and surgeon volume are not significantly associated with the incidence of severe perioperative complications in patients undergoing laparoscopic colectomy. Based on a retrospective analysis of 27 laparoscopic colorectal operations, performed between February 2007 and August 2010 in the Brežice General Hospital, we analysed the results of laparoscopic management of colon diseases in this small peripheral hospital.The aim of the study was to determine the relationship between the hospital and surgeon volume, and the incidence of severe perioperative complications, and to compare the results with those from a foreign multicentre study. Intraoperative and postoperative complications, adequacy oflymphadenectomy and 30- day mortality were recorded. The results were comparable to those reported in the literature: 30-day mortality was nil, lymphadenectomy was sufficient in all cases, the average patient age was 69 years, the average duration of operation was 150 min, and the hospital stay was 8 days. There were two postoperative complications (rectus abscess and pneumonia), which were successfully treated. One conversion was required because of a huge tumor growing into adjacent organs that was found intraoperatively. After comparison of our results with those reported in the literature, we can conclude that the hospital in Brežice offers optimal advanced treatment modalities to patients with colon disease. Hospital volume and surgeon volume were not significantly associated with the incidence of perioperative complications following laparoscopic colectomy.
Keywords: kolorektalne novotvorbe; debelo črevo; laparoskopska kirurgija; therapy; zdravljenje